2012
DOI: 10.1016/j.drugalcdep.2011.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficits associated with cannabis use in young adults

Abstract: Background Cannabis is the most widely used illicit substance and has been associated with cognitive impairment. It is unclear whether such impairment can occur in the absence of potential confounding influences of co-morbid axis-I disorders and use of other illicit substances. Method Young adult volunteers (18–29 years) were recruited from the general community on the basis of having no axis-I disorders or history of illicit substance use other than cannabis use. Subjects were then grouped according to pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
2
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 26 publications
7
76
2
5
Order By: Relevance
“…Differences between marijuana user groups have appeared in these other cognitive domains (18,23,57,58). Nevertheless, there is no reason to expect such a difference would emerge in the present study.…”
Section: Are the Deficits In Crystallized Intelligence Specific To Macontrasting
confidence: 51%
“…Differences between marijuana user groups have appeared in these other cognitive domains (18,23,57,58). Nevertheless, there is no reason to expect such a difference would emerge in the present study.…”
Section: Are the Deficits In Crystallized Intelligence Specific To Macontrasting
confidence: 51%
“…There is considerable evidence implicating the use of various cannabis derivatives in altered cognition and decision making, including risk taking behavior, irrational (or excessive) gambling, as well as impulsive and apathetic patterns of choice. This evidence comes mainly from human studies (Dougherty et al 2013;Grant et al 2012;Hermann et al 2009;Lane et al 2005;Moreno et al 2012;Solowij et al 2012;Whitlow et al 2004) and related work in animals (Boomhower et al 2013;Egerton et al 2006;Egerton et al 2005;Mishima et al 2002) that largely concurs with the results of the human studies. The role of cannabinoid signaling in decision-making pathways and the involvement of cannabinoid receptors in frontal cortical circuits of decision making have not received much attention to date.…”
Section: Introductionmentioning
confidence: 64%
“…81,82 Neither fMRI study found inhibitory control deficits in individuals with cannabis dependence (using go/no-go tasks), which is line with the results of nonimaging studies in similar populations. 83,84 However, individuals actively using cannabis showed increased activation during inhibitory control relative to controls in the ACC/pre-SMA, right IPL and putamen. 81 These findings can be interpreted as a compensatory neural mechanism, given that individuals with cannabis dependence did not show behavioural deficits.…”
Section: Inhibitory Control In Individuals With Cannabis Dependencementioning
confidence: 99%